FTO gene variation and measures of body mass in an African population - Hattersley Andrew T; Rayco-Solon Pura; Sirugo Giorgio; Fulford Anthony J; Hennig Branwen J; Frayling Timothy M; Prentice Andrew M (BMC, 2009)
Abstract Background Variation in the fat mass and obesity associated (FTO) gene has been reproducibly associated with body mass index (BMI) and obesity in populations of White European origin. Data from Asians and African-Americans is less conclusive. Methods We assessed the effect of 16 FTO polymorphisms on body mass in a large population of predominantly lean Gambians (Nmax 2208) participating in a long-term surveillance program providing contemporary and early-life anthropometric measurements. Results Sixteen FTO tagSNPs screened here, including several associated with BMI in Europeans, were not associated with birth weight (BWT), early weight gain in 1-2 year olds, BMI in adults (≥ 18 y), or weight-for-height (WFH) z-score across all ages. No association was seen between genotype and WFH z-score or other measures of body mass. The confidence limits indicate that the effect size for WFH z-score never exceeded 0.17 units per allele copy for any SNP (excluding the three SNPs with allele < 15%). with much the lowest allele frequency. The confidence interval of the effect size for rs9939609 did not overlap that reported previously in Europeans. Conclusion To our knowledge this is the first study of FTO gene variation in a well-characterised African population. Our results suggest that FTO gene variation does not influence measures of body mass in Gambians living a traditional lifestyle, or has a smaller effect than that detected in Europeans. These findings are not directly comparable to results from previous studies in African-Americans due to differences in study design and analysis. It is also possible that any effect of FTO genotype on body mass is of limited relevance in a lean population where little excess food is available, compared to similar ethnic populations where food supply is plentiful.